A relação entre o ensino da física e o futuro profissional dos educandos do Ensino Médio do município de Francisco Beltrão/Pr - Machado, Claudia Gonçalves (2021)
Physics is considered a fundamental science once its object of study involves natural phenomena that are present in everyone's daily life. Although the notorious importance of this subject, which is present in the most varied undergraduate courses, there is a lack of interest of the students in studying disciplines related to Physics in Higher Education. Based on the scenario presented, this study has aimed to investigate the relationship that third-grade high school students from public schools take between the contents of Physics and their professional future. It starts founded on the assumption that the absence of a link between the discipline and daily life is keeping students away from a professional future in the exact sciences area. Thus, it is intended to analyze which features interfere directly and indirectly on this aversion, and the possible ways to modify this panorama. For that, an investigative framework was organized with students and teachers from two State Schools in the city of Francisco Beltrão - PR, in order to investigate these different social actors and their behavior front the problems faced by the teaching of Physics. This is a qualitative study, which involves bibliographic and field research, through using questionnaires for data collection, from a representative sample of graduating students and audio interviews recorded with teachers from each school. The data analysis was carried out by Critical Discourse Analysis (CDA). It is expected, in addition to the announced assumption, to discuss possible ways to deal with this challenge, which is linked to the discipline of Physics with high school student’s professional life on the verge of choosing their professional future.